Designing health communication campaigns : what works? - Backer, Thomas E. (SAGE, 1992)
This work identifies successful tactics for mass media campaigns to convince people to obey doctors' orders. The emphasis is on substance abuse, but AIDS, smoking, teenage pregnancy, heart disease, Alzheimer's disease, and seat belts are also considered.